2022
DOI: 10.3390/en16010377
|View full text |Cite
|
Sign up to set email alerts
|

Air/Water Heat Pumps in Existing Heating and Hot Water Systems for Better Urban Air Quality and Primary Energy Savings: Scenarios of Two Italian Cities

Abstract: In a previous work, a significant contribution to urban air pollution, related to fuel-fired heating systems, was recorded. Thus, the replacement of existing boilers for space heating and domestic hot water (DHW) production systems with high-temperature air/water heat pumps (which can operate with radiators, the most common terminals in the existing building stock), is proposed for the improvement of the urban air quality. Scenarios of substitution within the entire residential building stock of two Italian ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…Their research highlighted the dependence of the CO 2 emissions on the energy mix (55.2%), COP (33.9%), and climate change (10.9%). A study by Carella et al [10] presented the impact of replacing existing boilers for space heating and domestic hot water (DHW) production with high-temperature air-to-water HPs in two different Italian cities. Their results showed that Energies 2023, 16, 6233 2 of 15 the reduction of primary energy consumption varied between 34% and 60% for two values of renewable fraction in electricity generation (REN).…”
Section: Introductionmentioning
confidence: 99%
“…Their research highlighted the dependence of the CO 2 emissions on the energy mix (55.2%), COP (33.9%), and climate change (10.9%). A study by Carella et al [10] presented the impact of replacing existing boilers for space heating and domestic hot water (DHW) production with high-temperature air-to-water HPs in two different Italian cities. Their results showed that Energies 2023, 16, 6233 2 of 15 the reduction of primary energy consumption varied between 34% and 60% for two values of renewable fraction in electricity generation (REN).…”
Section: Introductionmentioning
confidence: 99%